Sand provenance and implications for paleodrainage in a rifted basin: the Tera Group (N. Spain) - González-acebrón, L.; Mas, R.; Arribas, J. (Journal of Iberian Geology, 2010)
Fluvial-fan and fluvial siliciclastic strata, developed during the rifting that generated the Cameros Basin (North Spain), record important provenance changes that reveal source areas compositions and locations, paleodrainage evolution and rift patterns. The Tera Group represents the first rifting stage in the Cameros Basin, containing fluvial-fan sediments at the lower part of the sedimentary fill that evolve to fluvial and lacustrine systems in the upper part of the record. Our quantitative sandstone petrographic analysis evidences the presence of three main petrofacies related closely to the rift basin evolution. At the base of the sedimentary succession, Petrofacies 1 (quartzolithic) indicates that the fluvial-fans source areas included Juras¬sic marine carbonates and older siliciclastic Mesozoic units, as well as metamorphic supplies from the West Asturian Leonese Zone (WALZ). Variscan basement sources of this metamorphic area (WALZ) were more abundant in the upper fluvial record (Petrofacies 2, quartzofeldspathic). Further, the influence of plutonic source areas with a mixed potassic and calcium-sodium composition is also recorded, probably related to the Central Iberian Zone (CIZ). In addition, a local sedimentary input was active during the fluvial and lacustrine stages (Petrofacies 2 and 3, both quartzofeldspathic), as a function of the palaeogeographical position of the Jurassic marine rocks and the level of erosion reached. Plutonic rock fragments have not been observed in the Tera Group sandstones of the western part of the basin. Thus, deeper erosion of the basement in the eastern Cameros Basin is suggested. The provenance evolution from quartzolithic to quartzofeldspathic petrofacies registered in Tera Group siliciclastic deposits is due to the higher influence of transversal supplies during the fluvial-fan stage (quartzolithic) to more important axial inputs during the fluvial stage (quartzofeldspathic). This provenance change represents the evolution from an undissected rift shoulder stage to more advanced stages of rifting (dissected rift shoulder) and during the beginning of a provenance cycle in a rifted basin.